Adolescent onset cognitive regression and neuropsychiatric symptoms associated with the A140V MECP2 mutation. (15th November 2013) - Venkateswaran, Sunita; McMillan, Hugh J; Doja, Asif; Humphreys, Peter
<x xml:space="preserve">Abstract</x> The phenotype attributed to MECP2 mutations continues to expand. In addition to classic and variant Rett syndrome, phenotypes include non‐specific intellectual disability and autism spectrum disorder in females, and fatal neonatal encephalopathy in males. One particular phenotype of parkinsonism, pyramidal signs, and neuropsychiatric symptoms (PPM‐X) has been described only in males. We report on the first female with the A140V MECP2 mutation presenting with late onset cognitive regression, pyramidal symptoms, parkinsonism, and bipolar symptoms. This finding emphasizes the need to consider MECP2 sequencing in females with non‐classic Rett phenotypes, particularly those with intellectual disability and neuropsychiatric features.